INTERNATIONAL TRENDS IN DEVELOPING THE NATIONAL QUALIFICATIONS SYSTEMS - Natalya M. Aksenova (Obrazovanie i Nauka, 2015)
The paper is devoted to a comparative analysis of international developments in establishing the qualifications systems; the related experience of the European Union countries are examined along with the main trends of the European discourse. The author demonstrates the mechanisms, guaranteeing the international comparability and compatibility of qualifications, and credits accumulation and transfer in vocational and higher education. The special emphasis is placed on developing principles of the national qualifications framework regarded as a basis of qualifications systems, the importance of the state participation and regulation of the na- tional qualifications systems development, maintenance and coordination is pointed out. The paper describes different models of the end-users participation in the national qualifications system formation, including the general public, employers, education administrations and employment bodies.